2020
DOI: 10.1038/s41598-020-62167-9
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vector Induced Modeling of High-Grade Spinal Cord Glioma in Minipigs

Abstract: Background: Prior studies have applied driver mutations targeting the RTK/RAS/PI3K and p53 pathways to induce the formation of high-grade gliomas in rodent models. In the present study, we report the production of a high-grade spinal cord glioma model in pigs using lentiviral gene transfer. Methods: Six Gottingen Minipigs received thoracolumbar (T14-L1) lateral white matter injections of a combination of lentiviral vectors, expressing platelet-derived growth factor beta (PDGF-B), constitutive HRAS, and shRNA-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…MRI of the spinal cord mass demonstrated radiological characteristics similar to those of xenografted glioma models (47,50). Lesions confirmed as highgrade glioma on histopathological analysis demonstrated invasion of white and gray matter, high cellularity, elevated Ki-67 expression, astrocytic morphology, and immunohistochemical evidence of GFAP and oligodendrocyte transcription factor 2 (OLIG2) expression (50). Lentiviral induction of a glioma model with multiple genetic abnormalities can be used to model the genotypic heterogeneity of glioma, allowing for the study of several common driver mutations (63).…”
Section: Large Animal Models Of Glioblastomamentioning
confidence: 83%
See 3 more Smart Citations
“…MRI of the spinal cord mass demonstrated radiological characteristics similar to those of xenografted glioma models (47,50). Lesions confirmed as highgrade glioma on histopathological analysis demonstrated invasion of white and gray matter, high cellularity, elevated Ki-67 expression, astrocytic morphology, and immunohistochemical evidence of GFAP and oligodendrocyte transcription factor 2 (OLIG2) expression (50). Lentiviral induction of a glioma model with multiple genetic abnormalities can be used to model the genotypic heterogeneity of glioma, allowing for the study of several common driver mutations (63).…”
Section: Large Animal Models Of Glioblastomamentioning
confidence: 83%
“…In rodents, retroviral expression of platelet-derived growth factor-β, HRAS-G12V, shRNA-p53 resulted in glioma formation (60)(61)(62). Employing a similar strategy, Göttingen minipigs were injected with lentiviral vectors expressing platelet-derived growth factor-β, constitutively active HRAS, and shRNA-p53 (50). MRI of the spinal cord mass demonstrated radiological characteristics similar to those of xenografted glioma models (47,50).…”
Section: Large Animal Models Of Glioblastomamentioning
confidence: 99%
See 2 more Smart Citations
“…Concerns about the ability of existing models to faithfully replicate human gliomas led us to produce the first lentiviral-vector-induced models of high-grade spinal cord glioma in rats and pigs [ 12 , 21 ]. Recently, we reported that the virus cocktail (PDGF-B, HRAS-G12V, and shRNA-p53) induces glioma in the minipig spinal cord [ 21 ].…”
Section: Introductionmentioning
confidence: 99%